Malignancies in Celiac Disease—A Hidden Threat with Diagnostic Pitfalls - Aleksandra Kubas; Ewa Małecka-Wojciesko (Biomedicines, 2025)
Celiac disease (CeD) is an autoimmune disorder that is triggered by gluten ingestion in genetically predisposed individuals. Untreated or poorly controlled CeD leads to various disease complications, such as malnutrition, osteoporosis, autoimmune diseases, or refractory celiac disease (RCD). Accumulating recent research has highlighted the association between CeD and the development of malignancies, particularly enteropathy-associated T-cell lymphoma (EATL) and small bowel carcinoma (SBC), which are neoplasms with extremely poor prognoses. Genetic alterations in the JAK1–STAT3 pathway and the high prevalence of microsatellite instability may be the main drivers of CeD-associated lymphomagenesis and small bowel oncogenesis and therefore could be an attractive therapeutic target to block cancer transformation. However, to date, the risk factors and exact mechanisms underlying malignancy development in patients with CeD remain unclear, and prospective cohort studies that include molecular profiling are needed. Moreover, current guidelines on the management of CeD do not provide standardized protocols for cancer surveillance—particularly regarding screening intervals, risk stratification, and monitoring strategies for high-risk patients such as those with RCD. This paper reviews the existing knowledge on malignancies in CeD, highlights diagnostic challenges, and discusses future perspectives on the early detection, monitoring, and treatment of CeD-associated neoplasms.